Seven samurai - Kurosawa, Akira, 1910-1998.; Motoki, Sojiro; Hashimoto, Shinobu, 1918-; Oguni, Hideo, 1904-1996.; Mifune, Toshiro, 1920-1997.; Shimura, Takashi, 1905-1982.; Jeck, Michael C.; Janus Films; Toho Kabushiki Kaisha; Criterion Collection (Firm); Home Vision (Firm) ([Irvington, N.Y.] : Criterion Collection, 1998)
This epic masterpiece is about a group of 16th century samurai who are hired to defend a small Japanese village that finds itself annually raided by an army of bandits who steal the meager crops harvested by the peasants. Tired of relinquishing their food supply but woefully inept in combat skills, the villagers decide to hire a band of samurai to protect them. In addition to the primary conflict between the villagers and the bandits, much of the tale revolves around young Katsushiro's coming-of-age, both sexually and emotionally. Kikuchiyo's search for acceptance forms the other major storyline. Indeed, everyone in Seven Samurai is searching: for adventure, for experience, for freedom from their oppressors.
Special features: Standard version (1.33:1) -- Audio commentary by Japanese film expert Michael Jeck -- Original U.S. theatrical trailer -- Optimal image quality: RSDL dual-layer edition -- Restored picture and sound -- Language: Japanese -- Subtitles: English.
Title also appears in Japanese characters on title screen.
Originally produced as motion picture in 1954.
A foreign film (Japan).
"A joint venture between Janus Films and Home Vision Cinema"--Container.
Special features: original U.S. theatrical trailer; audio commentary by Japanese film expert Michael Jeck.
Photography, Asaichi Nakai ; editor, Hiroshi Nezu ; music, Fumio Hayasaka ; historical research, Kohei Ezaki [and others].
Keywords: Samurai -- History -- 16th century -- Drama; Japan -- History -- Period of civil wars, 1480-1603 -- Drama; Feature films -- Japan; Foreign language films -- Japanese; Foreign films -- Japan